The Role of Sociology Teachers in Overcoming Student Delinquency Behavior - Fawziah Zahrawati B; Rosmala Dewi; Yuniar Yuniar; Sutriana Sutriana; Salwa Mayasari; Yusman Saputra (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2023)
ABSTRACTDelinquency among students is increasingly common. This if left unchecked will become something that is entrenched. This study aims to determine the portrait of student delinquency, the causal factors, and the role of the sociology teacher in overcoming student delinquency behavior. This research is a qualitative research. The research location is SMAN 3 Parepare City, South Sulawesi Province, Indonesia. The research informants were sociology teachers, school principals, and employees. Data collection techniques used include in-depth interviews, observation, and documentation. The collected data was analyzed qualitatively. Research has found that delinquency behavior by students includes being late to class, not doing assignments, cheating, and arguing. Factors that cause students to behave delinquently are the lack of attention from parents and the influence of the community environment. The role of the sociology teacher in overcoming student delinquency behavior is as a role model that provides an example of good character and as a facilitator who facilitates communication between students and guidance and counseling teachers, so that students can behave according to the values and norms that exist in society. The findings of this study can be additional information to overcome delinquency behavior that is rife among students.Keywords: Delinquency behavior; factors causing delinquency; the role of the sociology teacher.Â Â